Метрологічні аспекти зворотного інжинірингу стандартизованих виробів - Іванов, Віктор Володимирович; Чумак, Наталія Володимирівна (НТУ "ХПІ", 2017)
Уточнено поняття зворотного інжинірингу. Показано як на підставі метрологічних вимірювань за допомогою бібліотек стандартних елементів та стандартних методів розрахунку, що реалізовані в САПР, може бути побудована концептуальна модель виробу. Послідовність процедур метрологічних, розрахункових та евристичних, яка при цьому виконується, формалізована у вигляді евроритму.

The aim of the work is the development of an algorithm of reverse engineering for standardized products. To create metrological models, and even more to solve the complex task of reverse engineering, it is necessary to have not only metrological measurements and calculations using CAD, but also heuristic techniques that allow to recreate the conceptual model and design a new product instead of the damaged one taking into account real technological capabilities. These heuristic techniques are the selection of elements, the establishment of interrelations between elements, the identification of interrelated and independent groups of elements, the definition of inputs and outputs of the system, the use of models in the form of matrices and graphs. The relationship between realistic, conceptual, ideal and normative models is found in the case when the input data are the actual dimensions of the existing product, which are measured with certain errors. As a result of the work it is obtained the heuristic algorithm of the reverse engineering process for gear transmission; it is established that in order to determine the parameters of an ideal model, along with metrological measurements that allow us to find a realistic experimental model, it is necessary to use heuristic techniques and CAD; for complex engineering products with a high degree of standardization, reverse engineering is connected first of all with the use of databases of standard parts, elements of parts, steel grades, and the standard methods of calculation contained in CAE modules.
Metrological aspects of reverse engineering of standardized products
Keywords: САПР; концептуальна модель виробу; послідовність процедур; координатно-вимірювальне обладнання; евроритм; CAD; conceptual model; sequence of procedures; heuristic algorithm; reverse engineering